Awareness of care labels among high-income consumers - Reyes, Ma. Rayminda; Florendo, Racquel B. (1997.)
The study was conducted to determine consumer awareness towards care labels among high-income males and females. Also, this study tackles other related aspects like the use of care labels and attributes used for purchase decision criteria for selecting a garment among these selected consumers. Subjects were ninety-four, 29 males and 65 females working within companies located in Makati City, Ortigas, Greenhills and in some areas within Metro Manila. They are the sample group representing high-income consumers within the age range of 25-45 years old who have atleast an annual income of P100,000 and above. Findings show that consumer group of this study are aware of the existence of care labels and know the main function of care labels. Seventy-five percent of them mentioned that care instructions in the label are sufficient and can easily be understood. Consumers feel the need of importance that all clothes locally manufactured be affixed with care label instructions. Results show also that majority of the group prefer labels sewn in garments. They are willing to spend money for the garment's care labels. Eighty percent of them have used care labels a number of times. Quality is the most important attribute for purchase decision of a garment. Sixty-seven percent look for labels with price and size most frequently. On the other hand, cotton is the most familiar fiber and the easiest fiber to care among male and female consumers. And Machine Wash Warm is the most familiar care instruction for them. Evidences show that consumer education is needed. It is also recommended that further studies be made regarding the comparison of consumer awareness between high-income and middle-income groups towards care labels as well on the application of care labels among local garments manufacturers.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing care labels; Clothing and dress--Care.